2017
DOI: 10.7324/japs.2017.70720
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of self-medication among the college students in Tehran

Abstract: Background: Self-Medication is medicine consumption without prescription regardless of the cause, amount, and duration of use. This study was conducted to determine the prevalence of self-medication and associated factors among a sample of students of Tehran in 2016. Methods: This is a cross sectional descriptive study was conducted with participation of 1269 students from three universities in Tehran, Iran. The samples were selected by cluster sampling method. Data collection tool in this study was a research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…18 Another study conducted on students in Tehran found that self-medication prevalence in women, single individuals, and students in medical universities was significantly higher compared to other participants in the study. 21 In the present study, it was shown that the most common sources of over-the-counter medications were pharmacies and medications left over from the previous use at home, respectively. According to a study by Okumura in Vietnam in 2002, self-medication was more common when the medication was kept at home and there were no adequate rules and efficient policies for controlling self-medication.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…18 Another study conducted on students in Tehran found that self-medication prevalence in women, single individuals, and students in medical universities was significantly higher compared to other participants in the study. 21 In the present study, it was shown that the most common sources of over-the-counter medications were pharmacies and medications left over from the previous use at home, respectively. According to a study by Okumura in Vietnam in 2002, self-medication was more common when the medication was kept at home and there were no adequate rules and efficient policies for controlling self-medication.…”
Section: Discussionmentioning
confidence: 53%
“…24 Another study found that people used self-medication to treat headaches, menstrual problems, and colds. 21 Another study in Iran revealed that the most important group of diseases for which the participants used self-medication were respiratory diseases. 25 In another study, self-medication was used to treat headaches, allergies, and fever.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the prevalence of opium, methamphetamine, and tramadol use was 2.2%, 7.2%, and 14.8%, respectively. Other studies showed that gender is a predictor of substance use in medical students (30,31).…”
Section: Discussionmentioning
confidence: 95%
“…Por otro lado, realizando un análisis geoespacial, la automedicación en estudiantes universitarios es una práctica que afecta a poblaciones de diferentes localizaciones, demostrando que el panorama en Latinoamérica prevalece (12,19,20,21,24,25,29,37,41), a pesar de tener mayores conocimientos respecto a los riesgos, comparado con la población de Europa (33), África (5,23,26,32) y Asia (27,28,30,31,35) Desde otro punto de vista, la resistencia antimicrobiana se ha convertido en un tema ampliamente discutido por su implicación epidemiológica en países como Ecuador y Colombia, lo que indica la existencia de un alto consumo de antibióticos de forma indiscriminada y sin prescripción (49)(50)(51). Teniendo en cuenta lo anterior, se esperaba un elevado uso de dichos fármacos en las investigaciones que hicieron parte de la revisión sistemática; sin embargo, se identificó un comportamiento totalmente opuesto a lo sugerido en tales informes epidemiológicos, encontrándose que los analgésicos son el grupo farmacológico más empleado por los jó-Panorama de la automedicación en estudiantes de educación superior: una mirada global venes universitarios que practican la automedicación.…”
Section: Discussionunclassified
“…Las investigaciones seleccionadas se realizaron en países como: Brasil, Chile, Colombia, Nigeria, Egipto, Perú, Sri Lanka, Etiopia, Irak, Pakistán, Uganda y Turquía. La automedicación sobrepasó el 50% en todos los estudios, donde se obtuvieron porcentajes de práctica de automedicación que oscilan entre: 62,9% y 96,8% (5,11,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Este comportamiento está influenciado por diversos aspectos, los cuales serán descritos a continuación…”
Section: Características De Los Estudios Incluidosunclassified